Apert syndrome: temporal lobe abnormalities on fetal brain imaging. (13th November 2014) - Stark, Zornitza; McGillivray, George; Sampson, Amanda; Palma‐Dias, Ricardo; Edwards, Andrew; Said, Joanne M.; Whiteley, Gillian; Fink, A. Michelle
Abstract Objectives Apert syndrome is characterized by craniosynostosis and complex hand and foot syndactyly, and an increased risk of brain, palate, heart, and visceral malformations, and intellectual disability. This study aims to describe the structural brain abnormalities detected by dedicated neuroimaging of fetuses with Apert syndrome. Methods Retrospective review of ultrasound and magnetic resonance imaging brain imaging obtained in six fetuses with a diagnosis of Apert syndrome. Results Five fetuses had attenuation of the septal leaflets, and two had corpus callosum dysgenesis. All six had temporal lobe expansion and overconvolution and temporal lobe clefts. The temporal lobe abnormalities preceded the development of cranial deformity in two fetuses. Conclusion Overexpansion and overconvolution of the temporal lobe is evident antenatally and is particularly conspicuous in the fetus when the normal brain is still relatively smooth (approximately 24 to 28 weeks of gestation). © 2014 John Wiley & Sons, Ltd.